2016
DOI: 10.1016/j.jaci.2015.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab reduces cysteinyl leukotriene and 9α,11β-prostaglandin F2 overproduction in aspirin-exacerbated respiratory disease

Abstract: Omalizumab reduces cysteinyl leukotriene and 9a,11b-prostaglandin F 2 overproduction in aspirinexacerbated respiratory disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 15 publications
2
69
2
4
Order By: Relevance
“…Interestingly, fewer subjects with extremely high levels of the two PGD2 metabolites (2,3-dinor-11β-PGF2α and tetranorPGDM) and LTE4 were observed in SA subjects reported to take omalizumab (Xolair), Figure 21 below. This finding strengthens the mechanism that removal of free IgE from the systemic circulation stabilises the mast cells, and perhaps other cell types as well (Hayashi et al, 2016;Holgate et al, 2005), leading to a reduction in amount of allergen stimulation. Verification of this effect is best assessed in follow-up studies with an appropriate study design that includes equally balanced groups.…”
Section: Treatment With Anti-igesupporting
confidence: 80%
“…Interestingly, fewer subjects with extremely high levels of the two PGD2 metabolites (2,3-dinor-11β-PGF2α and tetranorPGDM) and LTE4 were observed in SA subjects reported to take omalizumab (Xolair), Figure 21 below. This finding strengthens the mechanism that removal of free IgE from the systemic circulation stabilises the mast cells, and perhaps other cell types as well (Hayashi et al, 2016;Holgate et al, 2005), leading to a reduction in amount of allergen stimulation. Verification of this effect is best assessed in follow-up studies with an appropriate study design that includes equally balanced groups.…”
Section: Treatment With Anti-igesupporting
confidence: 80%
“…Omalizumab, a humanized recombinant monoclonal antibody that blocks immunoglobulin E activation of mast cells and basophils, is approved for the treatment of moderate to severe persistent asthma, with demonstration of efficacy in the treatment of CRSwNP . The role of omalizumab in AERD was reported in a case series of 21 patients by Hayashi et al . (level 4), demonstrating significantly improved nasal symptoms and corticosteroid utilization among 85.7% of patients 12 months after omalizumab.…”
Section: Discussion and Future Studymentioning
confidence: 99%
“…As previously discussed, subjects with AERD have greater tissue IgE levels compared with aspirin-tolerant patients with CRSwNP, 30 and targeting IgE with omalizumab may therefore be of particular interest in this severe subset of CRSwNP patients. In a study of 21 adult patients with AERD and allergic sensitization to at least 1 perennial aeroallergen, Hayashi et al 52 showed that treatment with omalizumab for 12 months induced significant reductions in urinary levels of leukotriene E4 and the prostaglandin D2 metabolite 9a,11b-prostaglandin F2, both markers of mast cell activation. In addition, the subjects also had reductions in exacerbations, hospitalizations, systemic corticosteroids, and nasal and asthma symptom scores.…”
Section: Anti-igementioning
confidence: 99%
“…In addition, the subjects also had reductions in exacerbations, hospitalizations, systemic corticosteroids, and nasal and asthma symptom scores. 52 A recent small, placebo-controlled study of 11 subjects with AERD looked at the effect of omalizumab on aspirin-induced respiratory reactions in subjects with AERD. Of the 7 subjects treated with omalizumab, only 2 of 7 (29%) had respiratory symptoms on ingestion of aspirin compared with all 4 (100%) subjects on placebo.…”
Section: Anti-igementioning
confidence: 99%